Africa Can Help Feed Africa : Removing Barriers to Regional Trade in Food Staples - World Bank (World Bank, Washington, DC, 2017)
Africa's growing demand for food has been met increasingly by imports from the global market. This, coupled with rising global food prices, brings ever-mounting food import bills. In addition, population growth and changing demand patterns will double demands over the next 10 years. Two key issues must be addressed: (a) establishing a consistent and stable policy environment for regional trade in fertilizers; and (b) investing in institutions that reduce the transaction costs of coordination failures. Many countries have enacted new fertilizer laws in recent years, but few have provided the resources to define and enforce regulations through standards and testing capacity. This report shows that reducing regulatory burdens on fertilizers and the consequent increase in use of fertilizers will have substantial impacts on returns to farmers, with consequent impacts on poverty. The report highlights the range of barriers to food trade in Africa along the entire value chain. The issues pertain to many ministries and agencies within government: trade, agricultural, health and safety, transport, and finance. This in turn requires a "whole of government' approach to freeing up food trade, which will require strong and effective leadership to articulate the rationale and sustain the momentum for reform. Leaders must also address the hard choices that will arise in dealing with the political economy constraints that have until now blocked the capacity of Africa to exploit its enormous potential to feed Africans.